2018
DOI: 10.1097/igc.0000000000001341
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Results and Prognostic Factors of Brain Metastases From Ovarian Cancer: A Single Institutional Experience of 56 Patients

Abstract: ObjectivesThe most appropriate treatments for brain metastases from ovarian cancer have not been established mainly because of its rarity. The objective of this study was to describe clinical results of treatment and prognostic factors of patients with brain metastases from ovarian cancer treated at a single institution.Materials and MethodsWe retrieved information from the electronic medical records of 56 consecutive patients (2.8%) with brain metastases, from a total of 2008 patients with ovarian cancer. End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
(21 reference statements)
2
12
0
Order By: Relevance
“…This is a limit because macroscopic residual tumor after surgery is an independent prognostic factor in ovarian cancer [31], although it is unlikely to impact specifically on the development of brain metastases. Fourth, nearly all patients in our study have serous cancers, a good prognostic factor for patients with CNS involvement [11]. We could have selected a population with better prognosis, but in any case it appears to be well balanced to the control group as regards histology (see Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a limit because macroscopic residual tumor after surgery is an independent prognostic factor in ovarian cancer [31], although it is unlikely to impact specifically on the development of brain metastases. Fourth, nearly all patients in our study have serous cancers, a good prognostic factor for patients with CNS involvement [11]. We could have selected a population with better prognosis, but in any case it appears to be well balanced to the control group as regards histology (see Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…serous histology, older age at diagnosis [7][8][9][10] and nonsurgical treatment [11]. Median overall survival (OS) is about 5 months for women undergoing a single-modality treatment versus 22 months if a multimodal approach is pursued [10,11].…”
mentioning
confidence: 99%
“…This is a limit because macroscopic residual tumor after surgery is an independent prognostic factor in ovarian cancer (32), although it is unlikely to impact specifically on the development of brain metastases. Forth, nearly all patients in our study have serous cancers, a good prognostic factor for patients with CNS involvement (11). We could have selected a population with better prognosis, but in any case it appears to be well balanced to the control group as regards histology (see Table 5)…”
Section: Discussionmentioning
confidence: 99%
“…Recently, brain involvement seems to increase (6), probably due to improvement of medical treatments, radiotherapy and surgery (3,(7)(8)(9)(10). Negative prognostic factors in patients with CNS involvement are extra-cranial disease, single-treatment approach, multiple brain lesions, low Karnofsky Performance Status, non-serous histology, older age at diagnosis(7-10) and non-surgical treatment (11). Median overall survival (OS) is about 5 months for women undergoing a single-modality treatment versus 22 months if a multimodal approach is pursued (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Reports on surgical treatment for distant metastasis from ovarian cancer are limited. Kwon et al [ 6 ] reported that surgical resection for single or symptomatic brain metastasis from ovarian cancer prolonged survival. Burton et al [ 7 ] reported the outcomes of 20 cases of surgical treatment for recurrent ovarian cancer, including 11 patients with hepatic metastasis and 1 patient with pulmonary metastasis, and the 5-year overall survival rate was 45%.…”
Section: Introductionmentioning
confidence: 99%